Effect of the agitation on the adsorption and hydrolytic efficiency of cutinases on polyethylene terephthalate fibres - O'Neill, Jaime Alexandre Antunes (2007)
The effect of agitation on adsorption, desorption and hydrolytic efficiency of a native and a genetically modified cutinase (L182A) on polyethylene terephthalate fibres is reported in this paper. The effect of mechanical agitation was studied using a shaker bath with orbital agitation and a Rotawash machine with vertical agitation with and without extra steel discs inside the reaction pots. The results obtained indicate that mechanical agitation combined with enzymatic action enhances the adsorption and activity of cutinases towards PET (polyethylene terephthalate) fibres. L182A showed higher adsorption than the native enzyme for all the levels of mechanical agitation. Lower units of L182A lead to similar yields of terephthalic acid formed in all levels of mechanical agitation. The highest increase of hydroxyl surface groups was found for the genetically modified L182A at the lowest level of mechanical agitation with a shaker bath. These results indicate that enzymatic functionalization of PET is favoured with a process with lower levels of mechanical agitation.